Shared Tasks of the 2015 Workshop on Noisy User-generated Text: Twitter Lexical Normalization and Named Entity Recognition - Baldwin, Timothy; Marneffe, Marie Catherine de; Han, Bo; Kim, Young-Bum; Ritter, Alan; Xu, Wei (Association for Computational Linguistics (ACL), 2015)
This paper presents the results of the two shared tasks associated with W-NUT 2015: (1) a text normalization task with 10 participants; and (2) a named entity tagging task with 8 participants. We outline the task, annotation process and dataset statistics, and provide a high-level overview of the participating systems for each shared task.